2011
DOI: 10.1007/s10653-011-9388-0
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and trace metal distribution in selected locations of Sundarbans mangroves and Hooghly estuary, Northeast coast of India

Abstract: Four sediment cores were collected from selected locations of Sundarbans mangroves and Hooghly estuary, northeast coast of India to establish (210)Pb geochronology and trace metal distribution in sediments. Core sites were chosen to reflect a matrix of variable anthropogenic input and hydrological conditions. The vertical distribution of (210)Pb(xs) ((210)Pb(total)-(226)Ra) provided reliable geochronological age to calculate the mass accumulation rates and historic trace element inputs and their variations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(37 citation statements)
references
References 63 publications
2
26
1
Order By: Relevance
“…are also dominant plant species in the Indian Sundarbans (Mandal et al 2012). Like other mangrove ecosystems, Sundarban is also highly degraded by anthropogenic activities, like industrial, domestic, and shipping activities (Baneerjee et al 2012, Banerjee et al 2012. Sundarban is rich in biodiversity and is a favorable habitat for the Royal Bengal Tigers.…”
Section: Study Areamentioning
confidence: 99%
“…are also dominant plant species in the Indian Sundarbans (Mandal et al 2012). Like other mangrove ecosystems, Sundarban is also highly degraded by anthropogenic activities, like industrial, domestic, and shipping activities (Baneerjee et al 2012, Banerjee et al 2012. Sundarban is rich in biodiversity and is a favorable habitat for the Royal Bengal Tigers.…”
Section: Study Areamentioning
confidence: 99%
“…Additionally, RDA results also showed that many metals, such as Ni, Cr, Cd and Cu, have a correlation with Fe. Several studies have proved that Fe oxy-hydroxides are a major controlling factor for trace metal accumulation (Banerjee et al, 2012).…”
Section: Redundant Analysis Of Explainable Variablesmentioning
confidence: 99%
“…hopanes) ( Table 3). Furthermore, the input of these metals may also be associated with washing of impermeabilized surfaces containing waste of tyres, fuels, lubricants and brake pads, which are carried to the estuary by rainwater runoff (Banerjee et al, 2012) and may be associated with the intense traffic of motor vehicles in the locality. According to Grilo et al (2013), two bridges that cross the Passagem Channel (Camburí and Passagem) were constructed and refurbished, respectively, around 1980, increasing automobile traffic in the region.…”
Section: Metalmentioning
confidence: 99%
“…EF ¼ ðM=ScÞ Sample =ðM=ScÞ Background This index is used as a tool for studies of trace metals in order to evaluate the anthropogenic contribution to metal accumulation (Baptista Neto et al, 2000;Karageorgis et al, 2009;Banerjee et al, 2012). Usually, Al or Fe is used as conservative lithogenic marker, however, in this work Sc was used as it is derived only from lithogenic sources (Buat-Menard and Chesselet, 1979) and …”
Section: Metalmentioning
confidence: 99%
See 1 more Smart Citation